In Silico and In Vivo Studies of Carboxymethyl Cellulose Based Hydrogels from Cassava Stem and Young Papaya Seed Extract for Diabetic Wounds - Rahmawati, Risma; Lestari, Annisa Firda; Anggraini, Putri Regita; Safitri, Rahmadita Irma; A'yunin, Alfi Rizki; Firdaus, Maulidan (Molekul, 2024)
ABSTRACT. Diabetic chronic wound care remains a global challenge due to higher rates of infection leading to amputations and death. The development of wound dressing materials with good biocompatibility, adequate mechanical strength, high absorption, and anti-inflammatory and antibacterial properties are criteria for ideal wound dressings in clinical applications. This study aimed to prepare hydrogel plasters based on carboxymethyl cellulose (CMC) from cassava stems (Manihot esculenta C.) with the addition of an active substance from young papaya seeds (Carica papaya L.) for diabetic wound healing. The methods used included CMC synthesis, extraction of young papaya seeds, preparation of nanoparticles, hydrogel optimization using Response Surface Methodology (RSM), in silico study, and in vivo tests. All products for each stage were characterized by FTIR and XRD. Hydrogels were characterized by testing pH, organoleptic, swelling ratio, gel fraction, biodegradability, FTIR, and SEM. The results of RSM optimization obtained hydrogel with the formula Na-CMC 3%, citric acid 2%, and stirring temperature 70. Based on the in-silico test results, the apigenin compound has the lowest binding energy, namely -9.4 kcal/mol, so it has the potential to heal diabetic wounds by triggering angiogenesis through the VEGFR2 signal. In vivo test results showed that the hydrogel with the addition of young papaya seed extract had the fastest wound healing rate compared to other treatments, marked by 100% wound closure on the 10th day. Keywords: carboxymethyl cellulose, cassava stem, diabetes wound, hydrogel, young papaya seeds.